Enhancement of photodynamic therapy in gastric cancer cells by removal of iron. Issue 1 (July 1997) - Tan, W C; Krasner, N; O'Toole, P; Lombard, M
Abstract : BACKGROUND: Aminolaevulinic acid (ALA) is an endogenous substrate in the haem biosynthetic pathway. Protoporphyrin IX (PPIX), the immediate haem precursor in the pathway, has photoexcitable properties. Exogenous ALA has been used previously as a precursor agent in photodynamic therapy (PDT). Its main advantage is a short half-life and hence reduced incidence of skin photosensitivity. ALA can be toxic, however, causing, for example, transient increases in liver enzyme concentrations when given systemically and this may be dose related. AIM: To assess whether accumulation of PPLX and ultimately the efficacy of PDT could be improved by modulating both ends of the haem biosynthetic pathway. METHODS: Gastric cancer cells (MKN 28) were incubated with ALA (0-1000 mumolar) and desferrioxamine (0-800 mumolar) for 24 hours before exposure to argon-pumped dye laser (630 nm) at different energy levels (0-40 J/cm2). Cell viability was assessed by use of the methyl-tetrazolium (MTT) assay four hours after exposure to light. RESULTS: Total PPIX accumulation increased linearly with increasing extracellular concentrations of ALA up to 1 mmolar (r = 0.973, p < 0.005). Adding 200 molar of desferrioxamine trebled PPIX accumulation over the same period of incubation. Cell viability after exposure to light decreased with low doses (0-30 mumolar) of desferrioxamine (r = 0.976, p = 0.024). However, higher doses of desferrioxamine (more than 40 molar) seemed to confer a protective effect against PDT. CONCLUSION: PDT using ALA can be improved by removal of available iron with desferrioxamine. The reason for the protective effect of desferrioxamine seen at higher doses is not clear.